The theory of non-executive co-authorship and criminal charges against leaders of social protests - Chanjan Documet, Rafael (2023)
The aim of this article is to analyses the theory of non-executive co-authorship and its viability as a criminal charge for leaders of social protests for crimes originating in this context. For this, a review of national and international jurisprudence and doctrine on the theory of non-executive co-authorship is carried out in order to show what concept of this figure is compatible with the traditional foundations of co-authorship. This, to then show when its application is possible, considering its dogmatic approaches and a human rights approach, in protest. In this regard, it is argued that it can only be charged under this title if there is sufficient evidence that shows that the social leader, under a common plan, participated in an essential and remote way in the executive phase of the attributed crime.